Collective self-esteem and perceived stress among the non-infected general public in China during the 2019 coronavirus pandemic: A multiple mediation model. (1st January 2021) - Chen, Haopeng; Zhao, Xiaolin; Zeng, Mei; Li, Jiwen; Ren, Xi; Zhang, Mengning; Liu, Yadong; Yang, Juan
Abstract: This study aimed to investigate the multiple mediating effects of perceived social support and anxiety between collective self-esteem and perceived stress during the 2019 coronavirus disease (COVID-19) pandemic. From February 18 to 25, 2020, 1921 participants aged 18–68 were recruited to complete the questionnaire online. The results showed that collective self-esteem reduced the perceived stress by increasing perceived social support and decreasing anxiety, and their chain mediation path. Our findings identified the important factors in reducing perceived stress and their relationship, which can be used to develop interventions to improve the mental health of the general public during the COVID-19 pandemic. Highlights: Collective self-esteem (CSE) was negatively related to perceived stress. CSE reduced perceived stress by increasing perceived social support. CSE reduced perceived stress by decreasing anxiety. Perceived social support buffered anxiety, which formed the chain mediation.